Report of rare palatal expression of Nevus of Ota with amendment of Tanino's classification - Mahima V Guledgud; Karthikeya Patil; Srikanth H Srivathsa; Suchetha N Malleshi (Wolters Kluwer Medknow Publications, 2011)
Nevus of Ota, a benign melanocytic pigmentary disorder with rare malignant transformation potential, affects 0.014-0.034% of the Asian and Black population and has a strong predilection for females. It occurs in the area innervated by the first and second division of the trigeminal nerve. Oral manifestation is rarely noted with only 14 cases reported till date. This report documents a case of Nevus of Ota with the infrequently noted oral involvement, in an Indian lady. Since oral manifestation is not acknowledged in Tanino's classification, the authors propose a modification to the same.